Surgical management of colorectal cancer: the Fudan University Shanghai Cancer Center experience - Wu, Yuchen; Liu, Fangqi; Cai, Guoxiang; Wang, Minghe; Zheng, Hongtu; Wang, Lu; Li, Xinxiang; Cai, Sanjun; Xu, Ye (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Abstract: The incidence and mortality of colorectal cancer (CRC) are increasing in China. Although surgery is the initially preferred intervention, systematic and individualized treatment has become far more important, on account of the considerable developments in radiotherapy and chemotherapy. Nowadays, treatment decisions are usually made following multidisciplinary team (MDT) meetings, especially in Fudan University Shanghai Cancer Center (FUSCC). With precise and specific imaging examinations, effective preoperative staging and restaging after neoadjuvant therapy have been the routine, resulting in individualized treatments guided by MDT. These advantages also result in less invasive and function-preserving surgery. Based on clinical evidence of targeted therapy compared with traditional chemotherapy, effective treatment of CRC with metastasis, especially liver and peritoneal metastasis (PM), became more effective. Screening of patients with hereditary CRC, special consultant for surgical procedure and surveillance of hereditary CRC families are routinely performed.